Adoption Status of Crop Production Practices in Direct Seeded Rice: A Case Study of Kapurthala District of Punjab (India) (Indian Journal of Extension Education, 2021)
The labor scarcity amid lockdown due to COVID-19 and reduced labor migration from other states made timely rice establishments a big challenge for the farmers in Punjab. The direct seeded rice (DSR) emerged as economically viable option for timely rice establishment, but several farmers faced difficulties in DSR during kharif–2020 and therefore, adopted diverse crop production and management practices. A detailed survey was conducted in different blocks of Kapurthala district (Punjab) and data were collected from randomly selected 106 farmers. The results showed that 13.2 per cent of total farmers completely failed in DSR. There was large variation in different crop production and management practices followed by the farmers. Seed rate varied between 19.9 and 22.2 kg ha-1 and was significantly higher in Kapurthala, while lowest in Dhilwan block. Nitrogenous fertilizer application was higher by 13.0 and 5.7 per cent in Sultanpur Lodhi and Nadala blocks than the district average of 167.9 kg N ha-1. Phosphoric and potash fertilizer application rates varied between 6.7 and 12.1 kg P ha-1 and 3.3 and 9.7 kg K ha-1, respectively. Rice grain yield varied between 64.3 and 70.2 q ha-1 under DSR, as compared with 71.3 and 76.3 q ha-1 under puddled transplanted rice (PTR). The irrigation water productivity varied between 3.6 and 4.4 kg ha-1 mm-1 in DSR, compared with 3.3 and 3.6 kg ha-1 mm-1 under PTR. The results highlight the lack of proper knowledge and adoption of recommended practices for DSR technology among farmers, which require further intensive extension efforts for creating awareness in between them.